1986
DOI: 10.1126/science.3726555
|View full text |Cite
|
Sign up to set email alerts
|

Bright Light Resets the Human Circadian Pacemaker Independent of the Timing of the Sleep-Wake Cycle

Abstract: Human circadian rhythms were once thought to be insensitive to light, with synchronization to the 24-hour day accomplished either through social contacts or the sleep-wake schedule. Yet the demonstration of an intensity-dependent neuroendocrine response to bright light has led to renewed consideration of light as a possible synchronizer of the human circadian pacemaker. In a laboratory study, the output of the circadian pacemaker of an elderly woman was monitored before and after exposure to 4 hours of bright … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
309
3
6

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 702 publications
(328 citation statements)
references
References 27 publications
10
309
3
6
Order By: Relevance
“…This blue-shift response was similarly observed in a study that compared a 2-h evening exposure to mono chromatic light of two different wavelengths (460 and 550 nm) at very low intensities, whereby subjects were more alert during the 460-nm than the 550-nm light (Cajochen et al, 2005). These findings corroborate to a wide range of non-visual light responses in humans, such as melatonin sup pression (Lewy et al, 1980;Zeitzer et al, 2000b), circadian phase shifting (Czeisler et al, 1986), nocturnal decline in EEG SWA (Cajochen et al, 1992;Münch et al, 2006), and circadian gene expression (PER2) in oral mucosa . Common to these responses is that they are all more sensitive to short wavelength light.…”
Section: Dose-and Wavelength Response Relationship Of Light Exposusupporting
confidence: 75%
“…This blue-shift response was similarly observed in a study that compared a 2-h evening exposure to mono chromatic light of two different wavelengths (460 and 550 nm) at very low intensities, whereby subjects were more alert during the 460-nm than the 550-nm light (Cajochen et al, 2005). These findings corroborate to a wide range of non-visual light responses in humans, such as melatonin sup pression (Lewy et al, 1980;Zeitzer et al, 2000b), circadian phase shifting (Czeisler et al, 1986), nocturnal decline in EEG SWA (Cajochen et al, 1992;Münch et al, 2006), and circadian gene expression (PER2) in oral mucosa . Common to these responses is that they are all more sensitive to short wavelength light.…”
Section: Dose-and Wavelength Response Relationship Of Light Exposusupporting
confidence: 75%
“…Reed Performance Assessment Battery (Thorne et al 1985), Immediately following the period of home treatment, subjects is sensitive to effects of bright light exposure during sleep returned to the laboratory for a 4-d protocol that was identical deprivation (Campbell and Dawson 1990;Badia et al 1991; to the pre-treatment protocol, with the exception that all Murphy et al 1995), as well as to the circadian rhythm of subjects were exposed to light during the first two nights in performance (Gillooly 1990;Badia et al 1991;Murphy et al the laboratory (i.e. the adaptation nights).…”
Section: Wilkinson Reaction Timementioning
confidence: 99%
“…To induce a clear shift in circadian rhythms, 3 days of bright light exposure at the appropriate time of day, while preventing light exposure during the other sensitive parts of the phase response curve, are sufficient in healthy subjects (Czeisler et al, 1986;Dijk et al, 1987). Light therapy induces quick mood changes in seasonal affective disorders in about the same time span (3-5 days) (Meesters et al, 1995), although longer treatment durations have been reported to result in further improvement (Bauer et al, 1994;Labbate et al, 1995).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Phase positions were assessed at the end of each condition only. According to empirical (Czeisler et al, 1986;Minors et al, 1994) and simulated data (Daan and Beersma, 1992), the washout period of 11 to 12 days in between ML and EL was considered to be long enough to recapture baseline phase positions at the start of the next condition. Not 1 subject showed an unexpected phase shift of DLMO after bright light exposure.…”
Section: Effects On Circadian Rhythmsmentioning
confidence: 99%
See 1 more Smart Citation